2018
DOI: 10.1096/fj.201700564rr
|View full text |Cite
|
Sign up to set email alerts
|

NK1R/5‐HT1AR interaction is related to the regulation of melanogenesis

Abstract: Substance P (SP) is a candidate mediator along the brain-skin axis and can mimic the effects of stress to regulate melanogenesis. Previously, we and others have found that the regulation of SP for pigmentary function was mediated by neurokinin 1 receptor (NK1R). Emerging evidence has accumulated that psychologic stress can induce dysfunction in the cutaneous serotonin 5-hydroxytryptamine (5-HT)-5-HT1A/1B receptor system, thereby resulting in skin hypopigmentation. Moreover, NK1R and 5-HTR (except 5-HT3) belong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 88 publications
0
3
0
1
Order By: Relevance
“…Иммунная и сосудистая системы кожи являются традиционными мишенями для серотонина в биорегуляторных процессах. Считается, что он опосредует меланогенез-модулирующие эффекты стресса, рецепторы 5-HT1A/1B особенно важны в связи между мозгом и кожей [10].…”
Section: Discussionunclassified
“…Иммунная и сосудистая системы кожи являются традиционными мишенями для серотонина в биорегуляторных процессах. Считается, что он опосредует меланогенез-модулирующие эффекты стресса, рецепторы 5-HT1A/1B особенно важны в связи между мозгом и кожей [10].…”
Section: Discussionunclassified
“…Studies have shown that in B10F16 melanoma cells, SP not only exerts a synergistic effect with CGRP, but also induces apoptosis in B10F16 cells and downregulates 5-hydroxytryptamine (5-HT)1A receptor and 5-HT2A receptor, both of which promote melanogenesis. This effect is mediated by binding to the NK1R receptor and activating S6 kinase 1 (S6K1) while inhibiting the MAPK signaling pathway 87 - 89 . Moreover, excess SP induced by mental stress decreases melanogenesis through keratinocytes.…”
Section: Novel Mechanisms Of Hair Pigmentation Regulationmentioning
confidence: 99%
“…In addition, 5-HT Ivyspring International Publisher receptors (5-HTRs) serve vital roles in these processes by binding to the surface of cell membrane [11]. According to recent studies, 5-HTRs were linked to malignant tumors, such as melanoma [12], breast cancer [13,14], lung cancer [15] and colon cancer [16]. For example, 5-HTR1B, 5-HTR3 and 5-HTR4 were proven to promote the proliferation of colorectal cancer cells (CRCs) [17].…”
Section: Introductionmentioning
confidence: 99%